ENGLISH SYNTAX ACQUISITION ORDER OF INDONESIAN ELEMENTARY SCHOOL LEARNERS - Syifa Khuriyatuz Zahro (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2018)
Linguistics’ research has proved that the acquisition order for foreign-language is not a static order but less consistent. Therefore, teachers of foreign language urgently need to understand the acquisition order of linguistics components to achieve an appropriate learning outcome, especially on syntactic mastery of the target language. For Indonesian learners, English sentence which employs verbs as its predicate is one of most complex linguistics component to learn and apply in their writing. The absence of a copula verb in Indonesian sentences which mostly ignored by some Indonesian learners affects the problem. Therefore, this study examines the English syntax acquisition order toward third and sixth grade of Indonesian learners in a descriptive qualitative approach. The participant is two learners of the third and sixth grade of Islamic Elementary School Lamongan who are requested to compose an essay writing three times to further analysis based on their grammatical function. The data is therefore in the form of writing produced by the participants about family, holiday and friend. The result indicates that both learners acquire five sentence patterns in their stage, they are S-V, S-V-sP, S-V-dO, S-V-dO-A, and S-V-A-sP. Meanwhile, the sentence pattern of S-V-sP is in the first order of acquisition by both levels of learners, while the last order acquired is the most complex one, S-V-A-sP.